PREPARATION FOR MODERNIZATION OF VERTICAL CNC MILLING MACHINE FP-17SMN4 - Tadjibayev Rasul Karimovich; Rakhmonov Zaylobiddin Obbosbek o’gli (Zeta Repository, 2023)
Deep modernization of the old machine with integration elements. Specific technological problems are one way to solve this problem general mechanical engineering and metalworking, in particular, to a modern level without significant investment.